A New Interpretation of Paul Wei’s Life and Work in New Religious Reform and Independent Church Movements - IAP, Sian-Chin (Journal of Research for Christianity in China (JRCC), 2025)
Most secondary sources that mention the founding of the True Jesus Church tend to briefly state that “Wei Paul founded the True Jesus Church in 1917,” without examining in detail the developmental process behind his motivation to establish the church. This article argues that, in the early stages of his ministry, Wei Paul did not intend to create a new denomination. Rather, he sought to promote a religious reformation movement, one that included breaking away from the influence of Western mission societies and pursuing ecclesiastical independence. The name he gave the church, “True Jesus Church,” was meant to signify the genuine church of Jesus, rather than a denominational title. Likewise, the term “Universal Correction Christianity” referred to the goal of correcting all churches across the nations—it served as the programmatic title of this reform movement. Through an analysis of Wei Paul’s life and ministry, this article offers a new interpretation, hoping to contribute a fresh perspective to the study of the True Jesus Church.